Energetic Analysis of Single Stage Lithium Bromide Water Absorption Refrigeration System. (2016) - Patel, Haresh A.; Patel, L.N.; Jani, Darshan; Christian, Amit
Abstract: A detail energetic analysis of LiBr-H2 0 absorption refrigeration system of 140 kW cooling capacity is investigated in the present study. The effect of exit temperatures of main components on heat load, circulation ratio, pump work, COP, COP rev and ηex are analyzed at different operating conditions. The result shows the heat load on generator and absorber increases with rise of generator and condenser exit temperature and it reduces when both evaporator and generator exit temperature are simultaneously increased. COP value is found high at lower condenser exit temperature and the average value of COP reduces by 8.1% when condenser temperature is increased along with generator exit temperature. As condenser exit temperature increases, the COPrev linearly decreases with it which results in hike of ηex by 38%. COP increases linearly with rise of evaporator and generator exit temperature but ηex keeps on decreasing with it. It was also found in the study that as the condenser and generator exit temperature increases, COP starts decreasing gradually but ηex first increases linearly with increase in the condenser exit temperature and then it starts to fall at the higher condenser exit temperature